The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.compbiomed.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of advanced glycated end product accumulation in skin using auto fluorescence multispectral imaging

Abstract: We proposed a non-invasive, contact-less novel technique for quantifying fluorescent AGE deposits in skin tissue using a multi-spectral imaging camera setup (MSI) during ultraviolet (UV) exposure. Imaging involved applying a region-of-interest mask, avoiding specular reflections and a simple calibration. Results of a study conducted on 16 subjects with skin types ranging from fair to deeply pigmented skin, showed that AGE measured with MSI in forearm skin was significantly correlated with the AGE reference met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The method was evaluated on data from SRD'15. The results from 16 subjects with skin types ranging from fair to deeply pigmented showed that AGE measured using MSI in forearm skin was significantly correlated with the AGE reference method on forearm skin [39] [38]. These results support the use of the technique for contactless measurement of the AGE content in either facial or forearm skin tissue over time.…”
Section: Multispectral Measurementsmentioning
confidence: 55%
See 1 more Smart Citation
“…The method was evaluated on data from SRD'15. The results from 16 subjects with skin types ranging from fair to deeply pigmented showed that AGE measured using MSI in forearm skin was significantly correlated with the AGE reference method on forearm skin [39] [38]. These results support the use of the technique for contactless measurement of the AGE content in either facial or forearm skin tissue over time.…”
Section: Multispectral Measurementsmentioning
confidence: 55%
“…The technique collects MSI images during UV exposure from a 365 nm LED (Smart Vision Lights). The method is presented in detail elsewhere [38]. In summary, the AGE level was assessed as the ratio of the fluorescence intensity (475 nm camera) to the illumination intensity (360 nm camera).…”
Section: Multispectral Measurementsmentioning
confidence: 99%
“…Till date, the LC-MS/MS offers the highest selectivity and sensitivity in AGE detection [70]. But when it comes to simple, cost-effective, point-of-care diagnostics, our method can detect few nanograms of the sample compared to other fluorescence emission-based techniques [71, 72]. The method is highly specific for the AGEs, such that sugars and proteins do not develop any colour as such which are the expected interferences in the clinical samples such as blood or serum for the proposed study (Additional file 1 section 7).…”
Section: Discussionmentioning
confidence: 99%
“…Example of a grayscale AGE‐index image of the volar side of the arm detected by a multiphoton fluorescence imager [148]. The colored region indicate the region of interest selected for the AGE‐index calculation.…”
Section: Optical Approaches In Diagnosticsmentioning
confidence: 99%